Knowledge of the body and disciplinary knowledge. The proposal from the pedagogy of the body in a research with primary school teachers - Ferri, Nicoletta; Gamelli, Ivano (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
A teaching able to give body to knowledge and meet children’s learning attitude in their immediate sensitivity to living bodily experience is often limited in schools to few hours of physical education. Using concrete proposals, on the contrary, we want to show that a teaching experience inspired by the Pedagogy of the Body can help to achieve objectives traditionally reserved to other disciplinary forms of knowledge (letters, science, art), through a way that privileges the pleasure of movement and of active discovery. In particular, the contribution presents a still ongoing research with primary school teachers based on the method of “Experiential anatomy”. We will describe how it is possible to integrate experience and a scientific topic using perception and bodily imagination as essential tools of knowledge.